Effects of different fluid replacements on serum HSP70 and lymphocyte DNA damage in college athletes during exercise at high ambient temperatures - Hee-Tae Roh; Su-Youn Cho; Wi-Young So; Il-Young Paik; Sang-Hoon Suh (Elsevier, 2016)
Purpose: The aim of this study was to investigate the effects of fluid replacement by water or sports drinks on serum heat shock protein 70 (HSP70) levels and DNA damage during exercise at a high ambient temperature. Methods: Ten male college athletes with an athletic career ranging from 6 to 11 years were recruited from Yonsei University. The subjects ran on a treadmill at 75% of heart rate reserve during 4 different trials: thermoneutral temperature at 18°C (T), high ambient temperature at 32°C without fluid replacement (H), high ambient temperature at 32°C with water replacement (HW), and high ambient temperature at 32°C with sports drink replacement (HS). During each condition, blood samples were collected at the pre-exercise baseline (PEB), immediately after exercise (IAE), and 60 min post-exercise. Results: Skin temperature significantly increased during exercise and was significantly higher in H compared to T and HS at IAE. Meanwhile, serum HSP70 was significantly increased in all conditions at IAE compared to PEB and was higher in H compared to T at the former time point. Significantly increased lymphocyte DNA damage (DNA in the tail, tail length, tail moment) was observed in all trials at IAE compared to PEB, and attenuated DNA damage (tail moment) was observed in HS compared to H at IAE. Conclusion: Acute exercise elevates serum HSP70 and induces lymphocyte DNA damage. Fluid replacement by sports drink during exercise at high ambient temperature can attenuate HSP response and DNA damage by preventing dehydration and reducing thermal stress. Keywords: Acute exercise, DNA damage, Fluid replacement, Heat stress, HSP70, Sports drink